FakET: Simulating cryo-electron tomograms with neural style transfer - Harar, Pavol; Herrmann, Lukas; Grohs, Philipp; Haselbach, David (Structure, 2025)
In cryo-electron microscopy, accurate particle localization and classification are imperative. Recent deep learning solutions, though successful, require extensive training datasets. The protracted generation time of physics-based models, often employed to produce these datasets, limits their broad applicability. We introduce FakET, a method based on neural style transfer, capable of simulating the forward operator of any cryo transmission electron microscope. It can be used to adapt a synthetic training dataset according to reference data producing high-quality simulated micrographs or tilt-series. To assess the quality of our generated data, we used it to train a state-of-the-art localization and classification architecture and compared its performance with a counterpart trained on benchmark data. Remarkably, our technique matches the performance, boosts data generation speed 750×, uses 33× less memory, and scales well to typical transmission electron microscope detector sizes. It leverages GPU acceleration and parallel processing. The source code is available at https://github.com/paloha/faket/.
Keywords: Algorithms; tomografie elektronová; Deep Learning; software; počítačové zpracování obrazu; deep learning; Electron Microscope Tomography; Image Processing, Computer-Assisted; elektronová kryomikroskopie; Software; algoritmy; Cryoelectron Microscopy